Growth and Nutritional Biomarkers of Preterm Infants Fed a New Powdered Human Milk Fortifier: A Randomized Trial. Issue 4 (October 2017) - Rigo, Jacques; Hascoët, Jean-Michel; Billeaud, Claude; Picaud, Jean-Charles; Mosca, Fabio; Rubio, Amandine; Saliba, Elie; Radkë, Michaël; Simeoni, Umberto; Guillois, Bernard; de Halleux, Virginie; Jaeger, Jonathan; et al.
ABSTRACT: Objectives: The aim of this study was to assess growth and nutritional biomarkers of preterm infants fed human milk (HM) supplemented with a new powdered HM fortifier (nHMF) or a control HM fortifier (cHMF). The nHMF provides similar energy content, 16% more protein (partially hydrolyzed whey), and higher micronutrient levels than the cHMF, along with medium-chain triglycerides and docosahexaenoic acid. Methods: In this controlled, multicenter, double-blind study, a sample of preterm infants ⩽32 weeks or ⩽1500 g were randomized to receive nHMF (n = 77) or cHMF (n = 76) for a minimum of 21 days. Weight gain was evaluated for noninferiority (margin = –1 g/day) and superiority (margin = 0 g/day). Nutritional status and gut inflammation were assessed by blood, urine, and fecal biochemistries. Adverse events were monitored. Results: Adjusted mean weight gain (analysis of covariance) was 2.3 g/day greater in nHMF versus cHMF; the lower limit of the 95% CI (0.4 g/day) exceeded both noninferiority ( P  < 0.001) and superiority margins ( P  = 0.01). Weight gain rate (unadjusted) was 18.3 (nHMF) and 16.8 g · kg −1  · day −1 (cHMF) between study days 1 and 21 (D1–D21). Length and head circumference (HC) gains between D1 and D21 were not different. Adjusted weight-for-age z score at D21 and HC-for-age z score at week 40 corrected age were greater in nHMF versus cHMF ( P  = 0.013, P  = 0.003 respectively). nHMF had higher serum blood urea nitrogen, pre-albumin, alkaline phosphatase, and calcium (all within normal ranges; all P  ⩽ 0.019) at D21 versus cHMF. Both HMFs were well tolerated with similar incidence of gastrointestinal adverse events. Conclusions: nHMF providing more protein and fat compared to a control fortifier is safe, well-tolerated, and improves the weight gain of preterm infants.